Balneotherapy Sebagai Terapi Nonfarmakologi Penurunan Nyeri Sendi - Maria Putri Sari Utami (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2014)
Balneotherapy is one of modality for musculoskeletal disease, because few studies focusing on elderly patients with joints disease (rheumatritis). This literature review aim to examine the effectiveness of methods of balneotherapy. The studies and experiments of balneotherapy carried out before the results are effective again a decrease in pain in the joints. Articles obtained from an electronic search through MEDLINE, CINHAL, SCHOLARGOOGLE and the inclusion criteria journal published in the period between the years 2003-2013. Four journals are consistently explain the benefits of balneotherapy reduce joints pain. The use of warm water as a medium which can cause vasolidation of blood vessels in increasing blood flow. Increased blood flow can remove inflammatory product such as bradykinin, histamine, and prostaglandins that cause local pain.